MODEL AND PACKAGE OF TRAINING OF TEACHERS QUALITY IMPROVEMENT IN THE PERSPECTIVE OF STRATEGIC MANAGEMENT AT MATAHARI TERBIT ELEMENTARY SCHOOL SURABAYA - Emy Roesminingsih (Universitas Pendidikan Indonesia, 2009)
Teacher has a very significant role for the success of students. In playing their functions and roles, the interrelated strongest indicators is the teachers’ quality showing their responsibility to perform all tasks and their knowledge which can be used as the art and the way they work. It can be said that the qualified teachers are those who master knowledge or having management strategy and its development. The need of a new paradigm for education is based on the change related to the educational condition and need in the society. One of the most strategic change is to improve the strategic management through training of teacher quality improvement in the perspective of strategic management. By having school autonomy owned by Matahari Terbit Surya Elementary School, Surabaya, the school has an opportunity to explore the effort of increasing the school's efficacy including the development of its human resource. It is expected that by the presence of competent teachers, they will be able to be the change agent for the improvement activities in their school as the realization of accountability effort in the environment.